Policy Instruments Reform for Growth and Renewable Energy Transition in the Southeast Asia Region - Ardyarum, Mahfita (Purnomo Yusgiantoro Center, 2026)
One of the strategies used to decrease the production of greenhouse gases is to promote the use of clean, renewable energy. Mitigation initiatives are also part of the action plan to meet the Paris Agreement, which aims to keep global temperature rise below 1.5°C. The growth of the new and renewable energy mix is influenced by a variety of factors, including the economy, technology, energy consumption behavior, financial support, and policy instruments implemented by a country. The novelty of this study lies in examining the effects of five policy tools (i.e., net metering, feed-in tariffs, renewable portfolio standards/quotas, tax incentives, and auctions) on renewable energy growth across Southeast Asian countries grouped by gross domestic product per capita level, which are high (i.e., Singapore, Brunei), upper-middle (i.e., Indonesia, Malaysia, Thailand), and lower-middle (i.e., Cambodia, Myanmar). A fixed-effect model under the Feasible Generalized Least Squares approach was used for panel data estimation with data spanning from 2010 to 2022. It was found that of the 5 policy instruments utilized, net metering, feed-in tariffs, and renewable energy portfolios had a substantial impact on the accelerating renewable energy growth. In comparison, auctions and tax incentives did not. According to the findings, the three types of policy instruments can be strengthened and utilized as recommendations to accelerate the transition to new and renewable energy.